2003
DOI: 10.1073/pnas.0237126100
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic mGlu5 receptors regulate adenosine A 2A receptor signaling

Abstract: D opamine-and cAMP-regulated phosphoprotein of M r 32,000 (DARPP-32) is a signal transduction molecule that is selectively enriched in medium-sized spiny neurons in neostriatum, and plays an obligatory role in dopaminergic signaling. Mice lacking DARPP-32 exhibit profound deficits in their molecular, electrophysiological, and behavioral responses to dopamine, drugs of abuse and antipsychotic medication, demonstrating the importance of DARPP-32 in most of the actions of dopamine (1).When DARPP-32 is phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 32 publications
4
91
0
1
Order By: Relevance
“…Previous studies have demonstrated a positive role for ERK activity in the metabotropic glutamate mGlu5 receptor and adenosine A2A receptor stimulation of DARPP-32 Thr-34 phosphorylation (37). Here we present a mechanism that describes how ERK can modulate PKA activity.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have demonstrated a positive role for ERK activity in the metabotropic glutamate mGlu5 receptor and adenosine A2A receptor stimulation of DARPP-32 Thr-34 phosphorylation (37). Here we present a mechanism that describes how ERK can modulate PKA activity.…”
Section: Discussionmentioning
confidence: 90%
“…wt of 32 kDa), which has been shown to be abundantly expressed in all striatal medium spiny neurons (Walaas and Greengard, 1984;Ouimet et al, 1998) and to play an essential modulatory role in DA transmission (Fienberg et al, 1998). A coactivation of adenosine A 2A and mGlu 5 receptors has been recently revealed to be responsible of the synergistic potentiation of the state of phosphorylation of DARPP-32 (Nishi et al, 2003) and c-fos expression (Ferré et al, 2002) in striatal neurons. The functional cross talk that links mGlu 5 and A 2A receptors may therefore underlie the behavioral recovery observed in the present study.…”
Section: Functional Interaction Between a 2a And Mglu 5 Receptorsmentioning
confidence: 99%
“…New findings provide evidence that coactivation of A 2A and mGlu 5 receptors produce synergistic effect on DARPP-32 phosphorylation, a signal transduction molecule that is selectively enriched in medium-spiny striatal neurons (Nishi et al, 2003) and potentiate c-fos striatal expression (Ferré et al, 2002). However, the functional evidence of these positive interactions on specific motor deficits such as akinesia occurring early in the course of PD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Group I mGlu (mGlu1 and mGlu5) receptors preferentially activate a PLC signaling cascade but also are known to activate other signaling cascades (27). mGlu5 receptors directly interact with adenosine A 2A receptors (28) and potentiate adenosine A 2A -receptor signaling in an ERK-dependent manner in indirect pathway neurons (9). Furthermore, functions of mGlu1 and mGlu5 receptors are differentially regulated by PKC, G protein-coupled receptor kinase, regulator of G protein signaling, and Src-family protein tyrosine kinase (27,29).…”
Section: Regulation Of Darpp-32 Thr-34 Phosphorylation By Glutamate Nmentioning
confidence: 99%
“…Activation of NMDA and AMPA receptors decreases DARPP-32 phosphorylation at Thr-34 and Thr-75 through Ca 2ϩ -dependent activation of protein phosphatase-2B (PP-2B) (calcineurin) and protein phosphatase-2A (PP-2A), respectively (8). Activation of group I mGlu-5 (mGlu5) receptors increases DARPP-32 Thr-34 phosphorylation by potentiating cAMP formation coupled to adenosine A 2A receptors in an extracellular signal-regulated kinase (ERK)-dependent manner (9). Activation of group I mGlu receptors also increases DARPP-32 phosphorylation at Thr-75 as well as Ser-130 [casein kinase-1 (CK1)-site] (10).…”
mentioning
confidence: 99%